Detector Performance Characterization for High Sensitivity Single-Photon Imaging - Walker, Katherine L.; Cherry, Simon R.; Mitchell, Gregory S. (IEEE transactions on nuclear science, 2014)
We are developing detectors for an un-collimated scanner for very high sensitivity single-photon imaging. The scanner consists of two large, thin, closely spaced, pixelated scintillation detectors of either thallium-doped sodium iodide (NaI(Tl)), sodium-doped cesium iodide (CsI(Na)), or bismuth germanate (BGO). The scintillator arrays are interchangeable to optimize performance for a wide range of isotope energies and imaging subjects. For each scintillator, flood histograms were obtained utilizing test gamma sources: 109 Cd, 241 Am, 57 Co, 133 Ba, 137 Cs, 22 Na, and beta source 32 Si. Using a 3 mm thick 21 ×41 NaI(Tl) pixelated array ( 2 mm ×2 mm pixels on a 2.2 mm pitch), read out by two adjacent Hamamatasu H8500 multi-channel photomultiplier tubes (MCPMTs), the energy resolution for 57 Co was 12.2% over the center of the MCPMTs and 45.3% for pixels over the gap, with flood histogram peak-to-valley ratios > 6.1 for the center of the MCPMTs and > 4.2 for the gap between the two MCPMTs. The NaI(Tl) detector consistently produced peak-to-valley ratios of > 1.6 in the center of the MCPMTs for all radioisotopes studied. CsI(Na) and BGO detectors had flood histograms of similar quality to NaI(Tl) at intermediate to high-energies, allowing for optimal imaging across a wide energy range. The measured sensitivity for point sources placed 10 mm from the detector approached 35% for low-energy isotopes and all scintillator materials, which results in an expected system sensitivity (two opposing detectors) of ~ 70% for these isotopes. The 5 mm thick BGO arrays had the greatest efficiency for high-energy isotopes due to the increased stopping power of this material. The measured spatial resolution for 99m Tc for the CsI(Na) detector (1.6 mm pitch) was 7.5 mm FWHM at the aluminum entrance window (1.5 mm from scintillator face), decreasing to 15 mm at a distance of 5 mm from the scintillator face. The NaI(Tl) detector showed similar spatial resolution. This spatial resolution is sufficient for imaging well-localized radiotracer distributions in thin objects, and the very high sensitivity can be used for fast dynamic imaging, or imaging using very low injected doses.